Musculoskeletal injuries in athletes from five modalities: a cross-sectional study - Goes, Rodrigo Araújo (2020)
Instituto Nacional de Traumatologia e Ortopedia. Centro de Trauma do Esporte. Rio de Janeiro, RJ, Brasil.